STRATEGI DAN PERAN PEREMPUAN DALAM INDUSTRI BATIK DI LAWEYAN SURAKARTA: PENDEKATAN TEORI MOSER - Cahya Azizah, Amanda Zani Zani Cahya; Nurhadi, Nurhadi (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
Laweyan is one of the oldest villages in Surakarta known as a center for batik production. With a long history and a network of active production houses, this area holds great potential in the development of culture-based creative economy. This research examines the role of women in the batik production process and the adaptive strategies they implement in facing various obstacles, using Moser's development theory which encompasses anti-poverty approaches, empowerment, and efficiency. Through a qualitative approach and in-depth interviews with women batik makers, this study shows that women play a strategic role in household economic aspects and cultural social sustainability. They contribute to poverty reduction through income from batik (anti-poverty), strengthening capacity through financial management and skills enhancement (empowerment), and creating efficiency in production through division of labor and time management (efficiency). The strategies implemented include organizing daily finances, balancing work and rest time allocation, and improving product quality. These findings enrich the study of gender and the creative economy by emphasizing how women's work in the traditional sector can be seen as a form of agency as well as a contribution to community based sustainable development.